5x+13=9x-39

Simple and best practice solution for 5x+13=9x-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+13=9x-39 equation:


Simplifying
5x + 13 = 9x + -39

Reorder the terms:
13 + 5x = 9x + -39

Reorder the terms:
13 + 5x = -39 + 9x

Solving
13 + 5x = -39 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
13 + 5x + -9x = -39 + 9x + -9x

Combine like terms: 5x + -9x = -4x
13 + -4x = -39 + 9x + -9x

Combine like terms: 9x + -9x = 0
13 + -4x = -39 + 0
13 + -4x = -39

Add '-13' to each side of the equation.
13 + -13 + -4x = -39 + -13

Combine like terms: 13 + -13 = 0
0 + -4x = -39 + -13
-4x = -39 + -13

Combine like terms: -39 + -13 = -52
-4x = -52

Divide each side by '-4'.
x = 13

Simplifying
x = 13

See similar equations:

| -7p+3p=8 | | 3lnx=2 | | 7z-8=3z+24 | | -2/5x-1=3 | | 777/6 | | -4(x+5)=3(x-11) | | 2x-0.3-2.6x=3.42 | | 2x*5=11 | | v+5=8 | | 8=-5/6z-12 | | 2-3(3x-4)+5=52 | | -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) | | 4(v-8)=-2v-26 | | 8x=-8x-7x | | xsquared+12=1 | | 2x^2=x+29 | | -7(v+4)+5(6-7v)=44 | | 5d+7x+6= | | -36-3x=64-8x | | 12-8-12= | | 5-3x/4=4 | | 66*10= | | 8x-(6x+7)=6x-47 | | ×/11=×/12-8 | | 6+8-78738+3837484849=0939v |

Equations solver categories